Ta có: x^5 + x + 1 = x^5 - x^2 + x^2 + x +1
= x^2(x^3 - 1) + (x^2 + x + 1)
= x^2(x-1)(x^2 + x + 1) + (x^2 + x + 1)
= (x^2 + x + 1)[x^2(x-1)+1]
= (x^2 + x + 1)(x^3 -x^2 + 1)
lam theo Le Huu Minh chien hoac ban cu lam cach nay la ra voi moi bai dang xa+x+1
x5+x+1=x5+x4+x3-x4-x3-x2+x2+x+1=x3.(x2+x+1)-x2.(x2+x+1)+(x2+x+1)=(x2+x+1).(x3-x2+1)
\(x^5+x+1\)
\(=x^5-x^2+x^2+x+1\)
\(=x^2\left(x^3-1\right)+x^2+x+1\)
\(=x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(\left(x^2+x+1\right)\left[x^2\left(x-1\right)+1\right]\)